2001
DOI: 10.7547/87507315-91-9-445
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Osteomyelitis in Diabetes Using Erythrocyte Sedimentation Rate

Abstract: Osteomyelitis secondary to diabetic foot infections can lead to proximal amputation if not diagnosed in a timely and accurate manner. The authors have found no studies to date that correlate a specific erythrocyte sedimentation rate with osteomyelitis. A retrospective chart review of 29 diabetic patients admitted to the hospital with diagnoses of osteomyelitis or cellulitis of the foot during a 1-year period was performed. Of the various lab values and demographic factors compared, erythrocyte sedimentation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…In this study, WBC and ESR exhibited moderate sensitivity and specifi city for DFI. Kaleta et al (2001) showed that an ESR greater than 70 mm/h has a sensitivity of 89.5% and a specifi city of 100% for osteomyelitis in diabetic patients. We determined osteomyelitis in seven patients in the DFI group.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, WBC and ESR exhibited moderate sensitivity and specifi city for DFI. Kaleta et al (2001) showed that an ESR greater than 70 mm/h has a sensitivity of 89.5% and a specifi city of 100% for osteomyelitis in diabetic patients. We determined osteomyelitis in seven patients in the DFI group.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with a limbthreatening infection, positive results of a probe-to-bone test may be taken as nearly sufficient for diagnosis, but the performance characteristics of this test have not yet been fully defined. A swollen foot in a patient with a history of foot ulceration, a "sausage toe" (i.e., a red, swollen digit) [246], or an unexplained high WBC count [235] or inflammatory markers [236] should also arouse suspicion of osteomyelitis (B-II). Finally, radiologically evident bone destruction beneath an ulcer should be considered to represent osteomyelitis unless proven otherwise [247].…”
Section: Osteomyelitismentioning
confidence: 99%
“…The primary indicators of improvement are resolution of local and systemic symptoms and clinical signs of inflammation. Blood test findings, including WBC counts [234,235] and inflam- matory markers, such as the erythrocyte sedimentation rate [122,236,237] and the C-reactive protein level [238], are of limited use for monitoring response, although is it reassuring to see elevated levels decrease and cause for concern when they do not. When a hospitalized patient is ready for discharge or an outpatient returns for follow-up, the clinician should accomplish 4 tasks (figures 1, 2, and 4).…”
Section: Follow-upmentioning
confidence: 99%
“…27,28 Kaleta et al suggested that an ESR level of 70 mm/h might be the optimal cutoff point to predict osteomyelitis with sensitivity of 89.5% and specificity of 100%. 29 The cut-off level of 90 mm/h for ESR had fair specificity for the prediction of major amputation.…”
Section: Resultsmentioning
confidence: 99%
“…25,30 The sensitivity of this finding was only 28% in one study and was less than 50% in another study. [29][30][31] Yesil S et al showed that the cut-off level of 90 mm/h for ESR had fair specificity for the prediction of major lower extremity amputations. 32 Another study of severe diabetic foot infections reported that the mean ESR in cases with osteomyelitis was only 56 mm/h.…”
Section: Resultsmentioning
confidence: 99%